1982
DOI: 10.1007/bf01402216
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary cystic teratoma

Abstract: SummaryAn uncommon case of intramedullary cystic teratoma with a history of intermittent symptoms is reported.Subtotal removal was performed with relief of symptoms for four years since operation.The histogenetic hypotheses of spinal cord teratomas are briefly reviewed, and the trigerminal origin of these tumours is stressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Lum bar spine MRI a, b -T2 sagittal and ax ial plane showed well de lin eated cys tic le sion; c -T2 TIRM se quence showed no intralesional fat; d -T1 sequence with fat sup pres sion af ter con trast ad mis sion showed no con trast en hance ment in the le sion [4]. In our re viewed lit er a ture there was no con sen sus between au thors on the most com mon lo ca tion of spi nal teratoma: cer vi cal [14], tho racic [2,[15][16][17][18][19][20][21][22][23][24], lum bar [1,2,[15][16][17][18][19][20][21][22][23][24] or co nus [1,14]. No sex spe cific dif fer ences were found in spi nal teratoma in ci dence [4] but there is a sig nif icant dif fer ence in mean age at the time of di ag no sis between male and fe male: 36.4±12.3 years for men and 41.3±11.6 for women [4].…”
Section: Discussionmentioning
confidence: 51%
“…Lum bar spine MRI a, b -T2 sagittal and ax ial plane showed well de lin eated cys tic le sion; c -T2 TIRM se quence showed no intralesional fat; d -T1 sequence with fat sup pres sion af ter con trast ad mis sion showed no con trast en hance ment in the le sion [4]. In our re viewed lit er a ture there was no con sen sus between au thors on the most com mon lo ca tion of spi nal teratoma: cer vi cal [14], tho racic [2,[15][16][17][18][19][20][21][22][23][24], lum bar [1,2,[15][16][17][18][19][20][21][22][23][24] or co nus [1,14]. No sex spe cific dif fer ences were found in spi nal teratoma in ci dence [4] but there is a sig nif icant dif fer ence in mean age at the time of di ag no sis between male and fe male: 36.4±12.3 years for men and 41.3±11.6 for women [4].…”
Section: Discussionmentioning
confidence: 51%
“…8 Ak et al 1 reported a lesion in the upper cervical cord at the C2-3 level, and in the other two cases the lesions were located in the lower cervical segments at the levels of C5-T2 4 and C6-T1. 12 To the best of our knowledge we present the third case published in the literature of an IMMT in an adult in which the lesion occurred in the upper segment of the cervical cord (C1-2) and the fifth case in which an IMMT was located in the cervical spinal cord.…”
Section: Discussionmentioning
confidence: 86%
“…10 In only four of the reported cases of spinal teratomas in adults was the lesion located in the cervical cord. 1,4,8,12 The authors of one of these reports documented multiple lesions extending from the medulla oblongata to the L-2 level. 8 Ak et al 1 reported a lesion in the upper cervical cord at the C2-3 level, and in the other two cases the lesions were located in the lower cervical segments at the levels of C5-T2 4 and C6-T1.…”
Section: Discussionmentioning
confidence: 99%
“…Only seven cases of cervical intramedullary teratoma have been reported. [ 3 4 5 6 7 8 9 ] Cervical intramedullary mature cystic spinal teratoma with congenital dermal sinus has not been reported. We report clinical, radiological, operative, and histopathological findings and review literature on the subject.…”
Section: Introductionmentioning
confidence: 99%